2020
DOI: 10.3389/fmolb.2020.00076
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Adipogenesis: The Anti-adipogenic Role of AMP-Activated Protein Kinase

Abstract: Obesity is now a widespread disorder, and its prevalence has become a critical concern worldwide, due to its association with common co-morbidities like cancer, cardiovascular diseases and diabetes. Adipose tissue is an endocrine organ and therefore plays a critical role in the survival of an individual, but its dysfunction or excess is directly linked to obesity. The journey from multipotent mesenchymal stem cells to the formation of mature adipocytes is a well-orchestrated program which requires the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(139 citation statements)
references
References 225 publications
5
112
0
Order By: Relevance
“…On the other hand, luteolin-OSO 3 Na treatment slightly increased AMPK phosphorylation, however not comparable to luteolin. These results were parallel to MAPK activation as reports had shown that activation of p38, ERK, and JNK MAPKs during adipogenesis was in the opposite manner with AMPK activation [ 15 , 23 ]. Effect of samples on MAPK activation was further analyzed by flow cytometry assessing the expression of phosphorylated MAPK (ERK1/2) in adipo-induced hBM-MSCs.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…On the other hand, luteolin-OSO 3 Na treatment slightly increased AMPK phosphorylation, however not comparable to luteolin. These results were parallel to MAPK activation as reports had shown that activation of p38, ERK, and JNK MAPKs during adipogenesis was in the opposite manner with AMPK activation [ 15 , 23 ]. Effect of samples on MAPK activation was further analyzed by flow cytometry assessing the expression of phosphorylated MAPK (ERK1/2) in adipo-induced hBM-MSCs.…”
Section: Resultssupporting
confidence: 74%
“…Results suggested that luteolin inhibited the adipogenesis in hBM-MSCs via downregulation of MAPKs. MAPK-linked adipogenesis inducement occurs along with downregulated AMPK activation [ 23 ]. In this context, the effect of luteolin and luteolin-OSO 3 Na on AMPK activation was also analyzed by western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…AMPK is a heterotrimeric protein complex that is composed of α, β, and γ subunits [ 34 ], and plays a key role in cellular energy homeostasis [ 35 ]. There is much evidence that activation of AMPK inhibits lipid accumulation (adipogenesis) in 3T3-L1 preadipocyte differentiation [ 36 ]. The α subunit of AMPK (AMPKα) contains its catalytic domain where AMPK becomes activated when phosphorylation takes place at T172 [ 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have identified AMPK activation as a target for the treatment of obesity [ 52 , 53 ]. Accumulating evidence suggests that activation of the AMPK pathway suppressed PPARγ, C/EBPα, and SREBP-1c expression, and thus inhibits lipid accumulation during adipogenesis [ 54 , 55 , 56 ]. In addition, studies have related AMPK activation with the level of adiponectin [ 47 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%